Precocious Natural Mummification in Hanging: An Exceptional Case from Northern Cyprus - Ceker, Deren; Tuller, Hugh H.; Deniz, Idris (University of Florida Press, 2023)
Mummification is regarded as a particular form of decomposition. External factors such as sun, wind, humidity, and temperature are known to accelerate or slow down the mummification period. The process can take weeks or months to complete. Consequently, the diversity of external factors makes postmortem interval (PMI) estimations difficult. This case study reports on the first example of precocious natural mummification in Northern Cyprus and involves a 20-year-old male found hanging from the railing in the stairwell of an unfinished building. The individual had been missing only seven days. The body underwent complete computed tomography scanning, autopsy, and toxicology analysis. A fractured hyoid with associated ecchymosis is documented, indicating death by asphyxiation. The crime scene environmental factors and seven-day weather report during which the individual was missing were assessed to understand the factors that influenced this rapid mummification. Reporting on this case contributes to PMI studies in studies in Cyprus and other locations with similar environmental factors. © 2023 University of Florida Press.
Keywords: desiccation; forensic anthropology; forensic sciences; mummification; postmortem interval